2002
DOI: 10.1007/s00134-002-1282-x
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized β2-adrenergic agonists achieve therapeutic levels in the pulmonary edema fluid of ventilated patients with acute respiratory failure

Abstract: These results provide the first evidence that levels of beta-adrenergic agonists that are physiologically efficacious in experimental models can be achieved with conventional delivery systems in ventilated, critically ill patients with acute respiratory failure from pulmonary edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 37 publications
(59 reference statements)
2
51
2
Order By: Relevance
“…In a recently published randomized, placebo-controlled clinical trial of aerosolized albuterol (in concentration that have previously been reported to reach a concentration of 1 mM in the pulmonary edematous fluid by Atabai et al) for the treatment of acute lung injury it has been reported that albuterol did not improve clinical outcomes in patients with acute lung injury. 5,19) These data contradict a previously published retrospective study that showed that similar doses of inhaled salbutamol in patients with Acute Lung Injury resulted in shorter duration and decreased severity of the Acute Lung Injury. 20) Unfortunately in both studies the occurence or the resolution of pleural effusions were not assessed.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In a recently published randomized, placebo-controlled clinical trial of aerosolized albuterol (in concentration that have previously been reported to reach a concentration of 1 mM in the pulmonary edematous fluid by Atabai et al) for the treatment of acute lung injury it has been reported that albuterol did not improve clinical outcomes in patients with acute lung injury. 5,19) These data contradict a previously published retrospective study that showed that similar doses of inhaled salbutamol in patients with Acute Lung Injury resulted in shorter duration and decreased severity of the Acute Lung Injury. 20) Unfortunately in both studies the occurence or the resolution of pleural effusions were not assessed.…”
Section: Discussionmentioning
confidence: 78%
“…In this context we tested the possible effect of the drug on the pleura under the appropriate conditions. 5) We concluded that the salbutamol effect on the parietal pleura would further accelerate the resolution of the pleural effusion. Then, the pleural space would be available for more edematous fluid to influx from the flooded alveoli in cases of ARDS, promoting edema fluid clearance.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…[11][12][13][14][15] However, the effects of beta-adrenergic agonists in the treatment of pulmonary edema in humans have not been assessed, and information demonstrating the importance of this vectorial sodium transport in the development of and recovery from pulmonary edema in humans is sparse and indirect. 16,17 In a double-blind, placebo-controlled study, we tested whether the prophylactic inhalation of the betaadrenergic agonist salmeterol at a dose shown to stimulate the clearance of alveolar fluid 18 decreases the incidence of pulmonary edema during exposure to high altitudes in subjects who are prone to high-altitude pulmonary edema. We also measured the nasal transepithelial potential difference (a marker of the transepithelial sodium and water transport in the distal air-ways) [19][20][21][22] at low altitude in subjects who were prone to high-altitude pulmonary edema, subjects who were resistant to this condition, and subjects who had had transient perinatal pulmonary hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…74 Aerosolized albuterol achieves therapeutic levels in the pulmonary edema fl uid of patients with ARDS receiving mechanical ventilation. 75 Moreover, prophylactic salmeterol inhalation has been shown to prevent high-altitude pulmonary edema in humans, demonstrating its eff ectiveness for primary prevention of at least one form of pulmonary edema. 76 However, in two multicenter randomized trials, selective b 2 -agonists for the treatment of established ARDS failed to produce a clinical benefi t and appeared to actually worsen outcomes.…”
Section: Inhaled Corticosteroidsmentioning
confidence: 99%